Analysis of Industrial Readiness 4.0 on Family Business - Nugraha, Aryan Eka Prastya; Wuryandini, Endang; Wahyuhastuti, Novika; Suciptaningsih, Oktaviani Adhi (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2019)
The purpose of this study is to provide a broader and deeper view of the readiness of family businesses in the face of the era of digital disruption 4.0. The sample used in this study was 93 family business units, with the method of Exploratory Factor Analysis (EFA) assisted by SMART-PLS. Based on the results of the hypothesis proposed that directly entrepreneurial and managerial competencies in the family business have a positive and significant effect on industry 4.0 readiness. Competence, especially in the implementation of managerial competencies for business owners. The managerial competency indicators is known as professional, social and personal. Indirectly, family businesses can implement business strategies that are by the characteristics of their business so they can adapt to rapidly changing conditions.Implementation of Information and Communication Technology (ICT) is considered to be crucial in facing the Industry 4.0.